The Effect of Corporate Growth and Profitability on Company Value in One Of The National Private Banks in Indonesia Period 2012 To 2019 - Ana Sulistiana; Tri Ningsih; Indri Ayu Tansyar; Senen Machmud (LPPM STMIK Mardira Indonesia, 2022)
This study aimed to determine and analyze the influence of company growth and profitability on company value at one of the well-known national private banks in Indonesia for the 2012-2019 period. In this study, data collection techniques were used to obtain research data in the form of secondary data obtained from financial report documentation. There are two types of data used in this study: qualitative data in the form of a general description of the company and quantitative data in the form of the company's financial statements consisting of a profit and loss balance. Then the data were analyzed according to research needs: company growth proxied by Assets Growth, Profitability proxied by ROA, and company value proxied by PBV. The results showed that company growth (Asset Growth) positively and significantly affected firm value (PBV). In addition, profitability (ROA) positively and significantly affects firm value (PBV). As a result, company growth (Asset Growth) and profitability (ROA) simultaneously have a positive and significant effect on firm value (PBV) at one of the national private banks in Indonesia for the 2012-2019 period. The implications of research on companies need to increase company growth and profitability on firm value. Companies must increase the company's total assets and high return on assets. From an investor's point of view, a company with good growth will produce a reasonable rate of return—the higher the company's ability to earn profits, the greater the return expected by investors.